One-Dimensional Oxide Nanostructures as Gas-Sensing Materials: Review and Issues - Choi, Kyoung Jin; Jang, Ho Won (MDPI, 2010)
In this article, we review gas sensor application of one-dimensional (1D) metal-oxide nanostructures with major emphases on the types of device structure and issues for realizing practical sensors. One of the most important steps in fabricating 1D-nanostructure devices is manipulation and making electrical contacts of the nanostructures. Gas sensors based on individual 1D nanostructure, which were usually fabricated using electron-beam lithography, have been a platform technology for fundamental research. Recently, gas sensors with practical applicability were proposed, which were fabricated with an array of 1D nanostructures using scalable micro-fabrication tools. In the second part of the paper, some critical issues are pointed out including long-term stability, gas selectivity, and room-temperature operation of 1D-nanostructure-based metal-oxide gas sensors.
Keywords: ELECTRONIC NOSE; SNO2 NANOWIRES; SENSOR; SURFACE; NO2; SENSITIVITY; PERFORMANCE; HYDROGEN; H2S